The Influence of Emotional Intelligence and Flow at Work on Innovative Work Behavior in MSME Entrepreneurs - Sulistiyorini, Diyah; Zahra, Gebi Angelina; Hakim, Gamma Rahmita Ureka; Ahmad, Abdul Munajat (Jurnal Sains Psikologi, 2024)
Innovative work behavior is an essential factor for entrepreneurial success. This research aims to examine (1) how emotional intelligence influences innovative work behavior, (2) how flow at work influences innovative work behavior, and (3) how emotional intelligence and flow at work influence innovative work behavior. The population of this research is MSME entrepreneurs in the city of Malang. Through a purposive sampling technique, 124 entrepreneurs were obtained as samples in this research with the criteria of having been in business for two years or more, having a business in the MSME category, and being under the guidance of the Department of Industry and Trade Cooperatives in Malang City. The scales used are the Innovative Work Behavior (IWB), Assessing Emotion Scale (AES), and WOrk-reLated Flow inventory (WOLF). The validity of the items in this research used Pearson correlation, and the reliability of the instruments on the three scales was measured using Cronbach's alpha formula. The results of statistical techniques of multiple regression analysis showed that emotional intelligence and flow at work significantly influence innovative work behavior, both partially and simultaneously. Partially, emotional intelligence contributes 17.4 percent to innovative work behavior. Meanwhile, flow at work can explain innovative work behavior variables by 16%. Simultaneously, these two variables influence 24.9 percent of innovative work behavior.